Ethical and legal aspects of the dispute about the conscience clause in Italy in the years 2014-2015 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2015)
The main aim of this article is to outline a global panorama of respecting fundamental human right to freedom of conscience and the presentation of the discussion on conscientious objection in the Italian health service. The conscience clause is born of the conviction that freedom of individual conscience takes precedence over the provisions of state law. Its deepest justification is the freedom and dignity of the human person. Today there are in many countries all kinds of attempts to reduce or completely negate the conscience clause. It seems that the current dispute about the principle of conscientious objection should be seen as one of the manifestations of contemporary cultural and ideological war.